Effective tissue antiischemic therapy of etiologically various vascular diseases of the brain - A. L. Vertkin (Кардиоваскулярная терапия и профилактика)
The article focuses on the one of crucial topics in modern healthcare — cerebrovascular diseases. Main pathogenetic ways are considered for vascular complications of the brain, with highlighted energy deficiency as main part of pathogenesis. Taking an evidence data, we evaluate efficacy of mexidol (LLC “Farmasoft”, Russia), an antioxidant for combination therapy of vascular injury of the brain that has been proven as one of the best in clinical practice.